Pengaruh Pelayanan Pendidikan dan Disiplin Kerja Pegawai terhadap Kepuasan Siswa Di SMPN 2 Gunungguruh Kabupaten Sukabumi - Nanang Rahmatika (BUANA INFORMATIKA CBI, 2017)
Education services by schools are services in the form of educational services provided by teachers assisted by education personnel. In order for educational services to run as expected, discipline is needed, especially employee work discipline among educators and education staff.The formulation in this study: (1)Is there an effect of educational services on student satisfaction at SMPN 2Gunungguruh Sukabumi; ; (2) is there anythe effect of employee discipline on student satisfaction studying at SMPN 2Gunungguruh Sukabumi and; (3) To what extent is the influence of education and discipline servicesemployee work on student satisfaction at SMPN 2 Gunungguruh Sukabumi. While the aim is to obtain information abouteverything related to educational services and the level of work disciplinethe following employees are related to the problem of student satisfaction. The approach in this research is survey and the type of research is descriptivequantitative. Data collection techniques with documentation studies, field observations, researchliterature and distributing questionnaires to89 respondents.From the multiple regression equation, the results are that: (1) Every time it occursimprovement in education services oneunits will be followed by an increase in the rate of change in student satisfaction of 0.550; (2) Every time there is an increase in the work discipline of one unit employee, it will be followed by an increase in the level of change in student satisfaction of 0.252. While the partial hypothesis test with "t test" forX1 with Y obtained t-count = 7.685, significance 0.000 <0.050. That is, reject Ho and accept H1. Because t-count = 3.183 > t-table = 1.667, education services have a significant and positive effect on student satisfaction. While X2 with Y obtained t-count = 1.991, significance 0.000 <0.050. That is, reject Ho and accept H1. Because t-count = 1.991 > t-table = 1.667, then Employee Work Discipline has a significant and positive influence on satisfactionStudent. While the integrative effect with the "F-test" significant 0.000 < 0.050 and F-count = 49.873> F-table = 3.950, then Ho is rejected and H1 is accepted. This means that education services and employee work discipline have a positive and significant influence on student satisfaction. The contribution of influence on student satisfaction at SMPN 2 Gunungguruh is carried out simultaneously, namely from education services and employee work discipline by 53.3%. Keywords: Education Services, DisciplineWork, Satisfaction